Targeting MDM2 homodimer and heterodimer disruption with DRx-098D in TP53 wild-type and mutant cancer cells - Sean F. Cooke; Thomas A. Wright; Gillian Lappin; Elka Kyurkchieva; Yuan Yan Sin; Jiayue Ling; Alina Zorn; Bria O’Gorman; William Banyard; Chih-Jung Chang; Helen Wheadon; Danny T. Huang; et al. (Molecular Therapy: Oncology)
Novel pharmacological strategies capable of inhibiting pro-oncogenic MDM2 beyond its p53-dependent functions represent increasingly attractive therapeutic strategies to treat solid and hematological cancers that are dependent upon MDM2/MDMX, regardless of TP53 mutational status. Utilizing a novel first-in-class cell-penetrating peptide disruptor of MDM2 homo- and heterodimerization (DRx-098D), we demonstrate the anti-proliferative potential of blocking MDM2 dimerization against a panel of human cancer cell lines that are TP53 wild type, mutant, or null. DRx-098D elicits its anti-cancer activity via a differentiated mechanism vs. idasanutlin (a phase 3 clinical candidate MDM2-p53 small-molecule inhibitor), inducing significantly superior growth inhibition against TP53 null HCT116 cells. Our preliminary data highlight, for the first time, the potential therapeutic utility of exploiting both MDM2 homo- and heterodimerization in TP53 wild-type and mutant cancers with an MDM2-derived disruptor peptide.